DESAIN PENGEMBANGAN KURIKULUM PAI BERBASIS TEACHER AND STUDENT-CENTER - Ikwan Efendi (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2017)
Design of curriculum development based Islamic religious education teachers and learners at the center of the learners become imperative applied in the education unit, because the subject is student learning in school. While the teacher becomes a facilitator should be able to direct, guide and a role model for their students. Islamic religious education curriculum development in general should be based on objectives and competencies, the relevance, efficiency, effectiveness, flexibility, integrity, continuity, synchronization, objective and democratic. Additionally, in particular the development of Islamic religious education curriculum principle of curriculum objectives, principles of curriculum content, didactic-methodical principles, principles with regard to media and learning resources, and evaluation principles. Keyword: Curricullum Development Design, Islamic Educations, Teacher and Student-Center